(untitled) (Journal of Parents and Teachers, 2026)
To move beyond teaching that relies solely on textbooks and the teacher, this school uses videos as a teaching resource. This approach is divided into three distinct levels: video as a support tool, video as a means of expression, and video as a tool for analysis. This new approach to education has been shown to improve oral and written expression, as well as fostering teamwork.